A possible important regulatory role of estrogen in obstructive sleep apnea hypoventilation syndrome - Pinyi Zhou; Hongmei Li; Hongyan Li; Yan Chen; Yunhui Lv (Frontiers in Medicine)
Obstructive sleep apnea-hypoventilation syndrome (OSAHS) is a prevalent clinical sleep breathing disorder that affects both pediatric and adult populations. If left untreated, OSAHS can induce or aggravate systemic dysfunction across multiple organ systems, with a particularly pronounced impact on cardiovascular health, thereby posing a substantial threat to overall human well-being. Notably, there exists a significant sex disparity in the prevalence and severity of OSAHS, with a higher incidence and greater severity observed in males. However, this disparity tends to diminish post-menopause. Research indicates that sex differences in OSAHS are associated with gonadal function, wherein estrogen exerts a protective effect by modulating pharyngeal muscle tone and mitigating oxidative stress. This regulatory role of estrogen partially reduces the incidence of OSAHS and attenuates its pathological impact. Conversely, OSAHS may adversely affect gonadal function, resulting in decreased estrogen levels, which can exacerbate the condition. This review examines the beneficial role of estrogen in the progression of OSAHS and explores the potential impact of OSAHS on estrogen levels.